2017
DOI: 10.2135/cropsci2016.05.0298
|View full text |Cite
|
Sign up to set email alerts
|

Low Genetic Differentiation and Evidence of Gene Flow among Barley Landrace Populations in Tunisia

Abstract: Tunisian barley (Hordeum vulgare L.) landraces, representing the oldest cultivated accessions, are growing in scattered populations across drought‐ and salt‐stressed environments and constitute a precious reservoir of potentially useful traits for breeding programs. The objective of this study was to elucidate genetic diversity and population structure of barley landraces across the landscape of Tunisia. Populations from 11 geographic zones were genotyped using 21 nuclear microsatellites. A high level of genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…However, the lowest gene flow was found between eastern Mediterranean landraces and the germplasms from CIMMYT and ICARDA and between these germplasms and the modern cultivars from north America. This agrees with the results reported by Parzies et al [ 51 ] and Ben-Romdhane et al [ 52 ], suggesting that the genetic differentiation among landrace SPs is due to farmer trade and is mainly influenced by geographic distances. Cultivars with a CIMMYT/ICARDA origin reported lower values of gene flow than the other SPs, as reported previously by Rufo et al [ 46 ] in bread wheat.…”
Section: Discussionsupporting
confidence: 93%
“…However, the lowest gene flow was found between eastern Mediterranean landraces and the germplasms from CIMMYT and ICARDA and between these germplasms and the modern cultivars from north America. This agrees with the results reported by Parzies et al [ 51 ] and Ben-Romdhane et al [ 52 ], suggesting that the genetic differentiation among landrace SPs is due to farmer trade and is mainly influenced by geographic distances. Cultivars with a CIMMYT/ICARDA origin reported lower values of gene flow than the other SPs, as reported previously by Rufo et al [ 46 ] in bread wheat.…”
Section: Discussionsupporting
confidence: 93%
“…Low genetic differentiation values were accompanied by considerable gene flow levels, which are confirmed by previous investigations concerning pearl millet landraces (Bashir et al 2015) and other crop species such as barley (Ben Romdhane et al 2017). This finding is expected especially for a highly allogamous species like P. glaucum L, which present an out-crossing rate higher than 85%.…”
Section: Population Structure Analysissupporting
confidence: 84%
“…These results are in agreement with population structure and neighbour-joining clustering, in which a higher level of admixture was found for landraces from different geographical regions. Accordingly, it has also been suggested that the low genetic differentiation among SPs is due to seed exchange by farmers, mainly influenced by geographic distances [49, 50]. When two SPs were compared, in general gene flow between landrace SPs was also higher than between modern cultivars.…”
Section: Discussionmentioning
confidence: 99%